SCONE: Secure linux containers with Intel SGX - Arnautov, Sergei; Trach, Bohdan; Gregor, Franz; Knauth, Thomas; Martin, Andre; Priebe, Christian; Lind, Joshua; Muthukumaran, Divya; O'Keeffe, Dan; Stillwell, Mark L.; Goltzsche, David; Eyers, David; et al. (Proceedings of the 12th USENIX Symposium on Operating Systems Design and Implementation, OSDI 2016, 2016)
In multi-tenant environments, Linux containers managed by Docker or Kubernetes have a lower resource footprint, faster startup times, and higher I/O performance compared to virtual machines (VMs) on hypervisors. Yet their weaker isolation guarantees, enforced through software kernel mechanisms, make it easier for attackers to compromise the confidentiality and integrity of application data within containers. We describe SCONE, a secure container mechanism for Docker that uses the SGX trusted execution support of Intel CPUs to protect container processes from outside attacks. The design of SCONE leads to (i) a small trusted computing base (TCB) and (ii) a low performance overhead: SCONE offers a secure C standard library interface that transparently encrypts/decrypts I/O data; to reduce the performance impact of thread synchronization and system calls within SGX enclaves, SCONE supports user-level threading and asynchronous system calls. Our evaluation shows that it protects unmodified applications with SGX, achieving 0.6×-1.2× of native throughput.
CRIS-Team Scopus Importer:2022-07-19